PLANNING OF THEORETICAL AND PRACTICAL TRAINING IN ORGANIZING THE EDUCATION PROCESS OF FUTURE ENGINEERS (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article discusses theoretical and practical training of future engineers in the organization of the educational process, their importance in planning and managing the educational process.